A Case Report: Unusual Case of Heterotopic Pregnancy with Chronic Ectopic Pregnancy - Putri Embun Pagi; Haviz Yuad (Universitas Andalas, 2023)
Background : Heterotopic pregnancy describes the occurrence of two pregnancies in different implantation sites simultaneously, mostly manifested as intrauterine and ectopic pregnancies (ampullary in 80%). The incidence has been documented due to the increase incidence of pelvic inflammatory diseases. Case: A 28-years-old primipara woman with suspected chronic ectopic pregnancy, differential diagnosed with ovarian cyst. Previously, the patient had complete abortion because abdominal and pelvic pain still present, she decided to seek treatment at RSUP dr. Mdjamil, from ultrasound was found suspected chronic ectopic pregnancy differentially diagnosed with ovarian cyst. Laparoscopy had done then, the intraoperative findings found that there was a chronic ectopic pregnancy in the left ampullary tubal and then left salpingectomy was performed.Conclusion: This case is one of the unusual clinical presentations of heterotopic pregnancy. This case highlights the importance of including heterotopic pregnancy in the differential diagnosis especially in patients with persistent abdominal and pelvic pain after complete abortion.